Impact of Human Capital on Entrepreneurial Earnings: Employing Parametric and Nonparametric Methods - Karahan, Hatice (Journal of Economics and Behavioral Studies, 2013)
Economics literature provides ample evidence regarding the important positive effect of human capital on earnings. However, the self-employed have been consistently omitted in such studies. To fill this gap, I examine the effect of human capital on entrepreneurial earnings using National Survey of College Graduates dataset. To estimate the coefficients on income levels, I take advantage of three different econometric methods, namely OLS, Heckit and matching estimators. Regression results on men show that having higher education brings more success in terms of self-employment earnings. Evidence shows that men do better when they are self-employed whereas women are better off when they are wage workers. The most lucrative majors for male entrepreneurs are architecture, math, physics, chemistry and most fields of engineering. Women entrepreneurs who enjoy higher earnings are mostly majored in architecture, medicine, law, psychology and counseling. However, no particular education level is found to contribute to female entrepreneurial earnings.